The route of cacique llampilanguen (1804): geographical reconstruction of a historical path. - Walter Daniel Melo; Juan Francisco Jiménez; Sebastián Leandro Alioto (Boletín Geográfico)
This is an inter-disciplinary work which links a historical problem with a scientific and technologic solution based on the contribution of geography and cartography. It emerged from an investigation on the relationship between native societies and cattle introduced by Europeans in the Pampas, and with the trade networks and moving of people and animals which took place during the period of Indian autonomy. For colonial times, there is no abundance of sources that reveal the paths followed by natives; that is what gives a special meaning to the document viewed here, which consists on the description of a journey made by Juan Llampilanguen in 1804. This cacique departed from Trupf-Trupf in the current IX Region in Chile, and arrived at the Laguna del Monte in the province of Buenos Aires. The goal of the work is to rescue a good part of the mentioned route, up to the Guardia del Monte, adding up an overall distance of about 1,450 km. In zones where the path was not clear, the criterion used kept in mind that, given the transfer conditions at that time, the route used by a group which moved on horseback and carrying animals could only spread through places which had water availability over short distances. The methodology included the use of historical sources with ancient mapuche place names, which in part were thankfully conserved over considerable time; the cartographic base was a SRTM elevation model and Google Earth shots; and the utilized Geographical Information System (GIS) was ArcGIS 10.0, whose buffer tools were used to connect the relevant locations. In this way, the diverse tools and applications in SIG have helped to recover the trace of old communication routes in regions which, being out of colonial control, were badly known by authorities of imperial bureaucracy, and were not kept in their cartography.